The construction of a user interface model in online automated universities’ students matching system / Nurul Hidayah Ahmad Alemi - Ahmad Alemi, Nurul Hidayah (2005)
User Interface (UI) research and the Design Rationale (DR) is important in the development of advanced user interfaces. The aim of the research is to construct the user interface model and the physical design based on the model-based approach and the rationale behind the design decisions. Model-Based User Interface Development Environment (MB-UIDE) provides methods for supporting the systematic development of the interface. However, the DR should consider as a part of design process. This research describes the user interface model construction in TADEUS model-based approach. It consists of task model, user model, data model and interaction model. The mutually combination of those model generates the user interface model. The physical design is derived from the user interface model together with the Macintosh design rationale. Physical designs in Macintosh produce the user-centered user interface. Thus, it can be hopefully reducing the user frustration while using the system.